Validity of early MRI structural damage end points and potential impact on clinical trial design in rheumatoid arthritis. Issue 6 (19th June 2015) - Baker, Joshua F; Conaghan, Philip G; Emery, Paul; Baker, Daniel G; Østergaard, Mikkel
Abstract : Objective: To evaluate the construct validity of the rheumatoid arthritis MRI score (RAMRIS) erosion evaluation as structural damage end point and to assess the potential impact of incorporation in clinical trials. Methods: In a randomised trial of early methotrexate-naïve RA (GO-BEFORE), RAMRIS scores were determined from MRIs and van der Heijde-Sharp (vdHS) scores from radiographs, at baseline, week 12, week 24 and week 52. Progression in damage scores was defined as change >0.5. Associations of X-ray and MRI outcomes with clinical features were evaluated for convergent validity. Iterative Wilcoxon rank sum tests and tests of proportion estimated the sample size required to detect differences between combination therapy (methotrexate+golimumab) and methotrexate-monotherapy arms in (A) change in damage score and (B) proportion of patients progressing. Results: Patients with early MRI progression had higher DAS28, C reactive protein (CRP) and vdHS at baseline, and higher 2-year HAQ. Associations were similar to those with 1-year vdHS progression. Differences in change in structural damage between treatment arms achieved significance with fewer subjects when 12-week or 24-week MRI erosion score was the outcome (150 patients; 100 among an enriched sample with baseline-synovitis >5) compared with the 52-week vdHS (275 patients). Differences in the proportion progressing could be detected in 234 total subjects with 12-week MRI in an enriched sample whereas 1-year X-ray required between 468 and 1160 subjects. Conclusions: Early MRI erosion progression is a valid measure of structural damage that could substantially decrease sample size and study duration if used as structural damage end point in RA clinical trials.